1996
DOI: 10.3109/00016349609033282
|View full text |Cite
|
Sign up to set email alerts
|

Cervical ripening and induction of delivery by local administration of prostaglandin E2 gel or vaginal tablets is equally effective

Abstract: Cervical ripening and induction of delivery by local administration of prostaglandin E2 gel or vaginal tablets in cases presenting with an unfavorable cervical state is equally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The time intervals, from commencement of cervical priming to induction of labour, and from commencement of cervical priming to eventual delivery, were also significantly shorter for women in the intensive regimen. We believe these results agree with findings of researchers who used prostaglandin ge1 3,4,13,14 . As the median number of pessaries used were not significantly different in either dosing regimens, we believe that the intensive dosing regimen will also improve the cost effectiveness of induction of labour by shortening hospital stays, in agreement with the study of Mackenzie et al 15 who found financial advantages with a two dose prostaglandin regimen compared with a single dose regimen.…”
Section: Discussionsupporting
confidence: 90%
“…The time intervals, from commencement of cervical priming to induction of labour, and from commencement of cervical priming to eventual delivery, were also significantly shorter for women in the intensive regimen. We believe these results agree with findings of researchers who used prostaglandin ge1 3,4,13,14 . As the median number of pessaries used were not significantly different in either dosing regimens, we believe that the intensive dosing regimen will also improve the cost effectiveness of induction of labour by shortening hospital stays, in agreement with the study of Mackenzie et al 15 who found financial advantages with a two dose prostaglandin regimen compared with a single dose regimen.…”
Section: Discussionsupporting
confidence: 90%
“…The definition of unfavorable cervix is controversial. Several studies have defined it as a Bishop score of at least 2 (28), 3 (13), 4 (21, 29), 5 (30,31), or even 6 (14,32). Our results are consistent with a previous report that pre-induction cervical ripening is more likely than placebo to improve the cervical score and result in delivery within 24 hours (12).…”
Section: Discussionsupporting
confidence: 91%
“…Results similar to those with a single application have been achieved, suggesting that the time required for cervical ripening is fixed, based on the required remodeling process of the cervix [3,9,19]. For this reason, one dose of PG was used every 12 h but it has never been evaluated in ambulatory methods and overall in pregnancies with first-trimester fetal death.…”
Section: Discussionmentioning
confidence: 99%
“…A small clinical study has compared 2-mg doses of gel prepared against a 3-mg tablet intravaginally and intracervically at a dose of 0.5 mg in primigravid women whose cervices were unfavorable for induction; the difference in both groups did not reach statistical significance [9,10]. Recently, misoprostol, a prostaglandin E 1 (PGE 1 ) analogue, was given vaginally for the induction of labor at term.…”
Section: Introductionmentioning
confidence: 99%